CONTRIBUTION OF LATGALE LAWYERS TO FOUNDATION AND DEVELOPMENT OF THE STATE UNTIL 1940 - Mazure, Līga (Via Latgalica, 2017)
Society, the state, and the law – these are the three interrelated interacting institutions. From the society comes the initiative for the foundation of the state. The society may be strongly motivated in this process or it may follow the dream of independence intuitively. The state then creates the legal system for organization of the society and the existence of the state. Active representatives of the society who participate in the foundation, formation and strengthening of the state make an integral part of this process. These are representatives of different occupations – clergymen, writers, cultural figures, lawyers, etc. The aim of this research is to study the contribution of the lawyers of Latgale to the foundation of the Republic of Latvia and its development until 1940. Literature that covers three fields has been used in the research. First of all, this is the literature on the most important historical facts of Latvia and Latgale about the period of the First Free Republic of Latvia, finding the most active people who participated in these events. Secondly, literature about the 1917 Latgale Congress is analysed in the study, considering its significance in the foundation of the State and summarising its participants. Thirdly, literature about lives of these participants was studied, analysing their origin, relation to legal education and assessing the contribution of the representatives of Latgale justice system to the foundation and development of the State until 1940. The following research methods are used in the study: analytical, historical and systemic methods. The National Awakening of Latgale is traditionally associated with the period from 1904 until 1917, that is, from the lifting of the printing ban until Latgale Congress in Rēzekne on May 9 and 10, 1917. However, the supported opinion that the Awakening of Latgale has been already initiated between the 60s and the 80s of the 19th century is expressed more and more convincingly. In this period considerable activities of the Latgalian spirit are felt that led to freedom from the status of the Inflanty of the Vitebsk Governorate and to acquiring the name of Latgale. Thus, two representatives of the Latgale system of justice are to be mentioned in this period – Gustavs Manteifelis and Pīters Miglinīks. The lawyers of Latgale made a significant contribution to the foundation and formation of the Republic of Latvia. At the 1917 Latgale Congress, the Provisional Land Council of Latgale was formed that together with the Provisional Land Councils of Vidzeme and Courland worked in the Latvian Provisional National Council, promoting the foundation of the Republic of Latvia. The lawyers of Latgale also participated in this congress and were elected to the Provisional Land Council of Latgale (for example, Jānis Grišāns, Antons Laizāns, Pāvils Laizāns, Juris Pabērzs), as well as worked in the government of the Republic of Latvia – holding high official positions (for example, J. Pabērzs (Minister of Justice, Minister of Social Welfare), Pauls Mincs (Minister of Labour), Antons Rancāns (Minister of Transportation)), and achieving notable success in their professional activities (for example, A. Laizāns, J. Grišāns, Broņislavs Trubiņš, etc.), thus strengthening the Republic of Latvia. Despite the limited financial, social and other opportunities of the people of Latgale at the time, a relatively large number (12 people) of legal representatives made a significant contribution to the foundation of the State. The lawyers of Latgale generally came from farmers’ families; this fact only testifies to their fighting spirit. Access to legal education was relatively difficult because the nearest educational institutions that offered it were the University of Saint Petersburg, the University of Moscow and the University of Tartu. And only at the end of the period under study, such education was offered at the University of Latvia. Still, the representatives of Latgale obtained academic legal education, even at the Master’s degree level. In one exceptional case, legal skills were self-taught (P. Miglinīks), besides, to an excellent level. This is confirmed by the achievements of this lawyer of Latgale in practical activity and the contribution to the formation of the State. The origins of Latgale lawyers of the period under study covered practically the whole of Latgale, because their places of birth were in the districts of Rēzekne, Daugavpils, and Ludza. Even though some of them left for work in Rīga, some of them stayed in Latgale; still, regardless of the place of residence, the connection with Latgale was not lost, but contribution to the formation of the state was made. The activity of the lawyers of Latgale in the period under study was diverse in its content, wide in its range, and directed at a common aim. Firstly, through their professional activity they provided legal services, being, for example, lawyers, notaries, legal advisors; as well as provided legal aid to society, for instance, translating the Russian law into the Latgalian language, representing in court pro bono. Secondly, the lawyers of Latgale held high official positions, for example, there were three ministers among them, as well as members of parliament, state controllers, and judges. Thirdly, they also actively performed public activity, for example, joining societies (including professional societies), participating in publication of newspapers and other printed matter, being writers, poets, and songwriters. The activity of the lawyers of Latgale covered not only the national scale of Latvia, but high achievements were made at the international level both in social (G. Manteifelis) and professional (P. Mincs) activity. Furthermore, they worked as jurists, for example, P. Mincs, whose work was published again in the modern times. The work of all lawyers of Latgale was directed at a common aim – state under the rule of law – by promoting its foundation and strengthening the newly formed State. The significant contribution of the lawyers of Latgale to the interest of the State is also confirmed by the high awards received. Firstly, for the contribution to the benefit of the Republic of Latvia, national awards were received, such as the Order of the Three Stars, The Cross of Recognition, Lāčplēsis Military Order, and the Cross of Merit of Aizsargi. Secondly, for achievements on the international level, high awards of other states were received such as the Hungarian Order of Merit, the Russian Cross of Saint George, the Order of the Lithuanian Grand Duke Gediminas, an honorary diploma of the Leipzig museum, thus with honour representing the name of Latvia abroad. The contribution of the lawyers of Latgale is significant – in the implementation of the National Awakening of Latgale, in the foundation of the Republic of Latvia, in the development and strengthening of the Republic of Latvia. These historical events significant to the Republic of Latvia occurred with active involvement of the lawyers of Latgale and their important contribution.